Effects of two different watering tray types on the behaviour of geese - Molnár, Marcell; Bogenfürst, Ferenc (Acta Agraria Kaposváriensis, 1999)
For the development of rearing and laying technologies under intensive conditions the examination of the behaviour of geese is of great importance. Feeding, drinking, resting, preening, playing and social behaviour types were examined with two different watering tray types (free flow and ventile). On comparison of the results obtained with those presented in the literature it could be established that changes in comfort behaviour types in geese in the first 6 weeks are similar to those observed in Pekin, Muscovy and mulard ducks. Differences were found in the frequency of occurrence of the various behavioural forms. The decrease observed in feeding, drinking and playing time and the higher proportion of resting time inform us that activity in geese is lower than in ducks in the first weeks of rearing. In accordance with the results of the experiment it may be suggested that ventile watering trays be used for geese, as is already the practice with ducks. The introduction of this watering method could help to minimise the extent offeed and water wastage, since it induces the feed searching behaviour pattern. Lack of this behaviour, as is common with intensively kept geese, causes boredom resulting in behavioural anomalies.
Keywords: geese; behaviour; watering tray type